How does the scapula move during the tennis serve? - Rogowski, I.; Creveaux, T.; Sevrez, V.; Chèze, L.; Dumas, R. (Medicine & Science in Sports & Exercise, 2015)
Purpose: This study aimed to describe the scapulothoracic kinematics during the tennis serve in highly skilled tennis players.